Identification and quality assessment of beverages using a long period grating fibre-optic sensor modified with a mesoporous thin film - Korposh, Sergiy; Selyanchyn, Roman; James, Stephen W.; Tatam, Ralph P.; Lee, Seung-Woo (Elsevier, 2014)
In this study, an optical fibre long period grating (LPG) sensor functionalised with a mesoporous thin film was employed for the identification and quality assessment of beverages. The principle of the discrimination of beverages using an LPG sensor is based on the measurement of the change in refractive index of a sensitive film, induced by the binding of the chemical compounds present in the beverage. The sensitive film deposited onto the LPG consisted of poly(allylamine hydrochloride) (PAH) and silica nanospheres (SiO2 NPs) with diameters ranging from 40 nm to 50 nm. PAH imparts selectivity, while the SiO2 NPs endow the film with high porosity and enhanced sensitivity. In this study, five different types of beverages, red and white wines, brandy, nihonshyu (sake, a Japanese rice wine), and shochu (a Japanese distilled beverage), prepared via distillation and fermentation, were used to assess the capability of the sensor to identify the origin of the beverages. In addition, a selection of red wines was used to evaluate the use of the sensor in the assessment of the quality of beverages. The results obtained were benchmarked against those obtained using gas chromatography–mass spectrometry for the determination of volatile compounds contributing to the flavours of a set of red wines. Principal component analysis (PCA) was employed for data analysis. This approach enabled both quality assessment of beverages and identification of the methods and materials used for their preparation.
Keywords: Long period grating; Mesoporous thin film; Layer-by-layer; Quality assessment; Beverages